2020
DOI: 10.1038/s41541-020-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with full-length Plasmodium falciparum merozoite surface protein 1 is safe and elicits functional cytophilic antibodies in a randomized first-in-human trial

Abstract: A vaccine remains a priority in the global fight against malaria. Here, we report on a single-center, randomized, double-blind, placebo and adjuvant-controlled, dose escalation phase 1a safety and immunogenicity clinical trial of full-length Plasmodium falciparum merozoite surface protein 1 (MSP1) in combination with GLA-SE adjuvant. Thirty-two healthy volunteers were vaccinated at least three times with MSP1 plus adjuvant, adjuvant alone, or placebo (24:4:4) to evaluate the safety and immunogenicity. MSP1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 98 publications
6
78
0
Order By: Relevance
“…MSP1 plays an important role in the invasion of erythrocytes as it binds and recruits other peripheral merozoite surface proteins to form a complex [109]. MSP1 starts off as a precursor of about 196 kDa and then cleave into four subunits before invading the erythrocytes [110]. The four subunits are held non-covalently forming a complex attached to the merozoite's GPI anchor [110].…”
Section: Pfmsp1mentioning
confidence: 99%
See 3 more Smart Citations
“…MSP1 plays an important role in the invasion of erythrocytes as it binds and recruits other peripheral merozoite surface proteins to form a complex [109]. MSP1 starts off as a precursor of about 196 kDa and then cleave into four subunits before invading the erythrocytes [110]. The four subunits are held non-covalently forming a complex attached to the merozoite's GPI anchor [110].…”
Section: Pfmsp1mentioning
confidence: 99%
“…MSP1 starts off as a precursor of about 196 kDa and then cleave into four subunits before invading the erythrocytes [110]. The four subunits are held non-covalently forming a complex attached to the merozoite's GPI anchor [110]. Once the MSP1 complex is formed, it binds with the receptors on erythrocytes and activates a spectrin-binding function to enter the erythrocytes [110].…”
Section: Pfmsp1mentioning
confidence: 99%
See 2 more Smart Citations
“…A myriad of biological and technical barriers have been encountered; however, step-by-step, these barriers have been chipped away. Advances include: new insights into the evolution of the immune response to the major pre-erythrocytic target, CSP 10 , and into the role of complementfixing antibodies in blood stage clinical immunity 11 ; the ability to express and manufacture full length versions of blood stage targets, e.g., the highly promising, highly conserved reticulocytebinding protein homolog 5 (PfRH5) 12 , as well as the 196-kDa merozoite surface protein 1 (the primary structure first described by Holder, et al in 1985 13 ), the latter of which demonstrated favorable safety and immunogenicity in a first-in human study 14 ; and, the delivery of target malaria parasite antigens by measles vectors to overcome the barrier of waning immune responses, resulting in durable memory and protection, at least in a murine model 15 .…”
Section: P Falciparum Vaccine Development Stage-by-stage and Step-bymentioning
confidence: 99%